Italian Studies on Quality of Life - Bianco, Adele; Conigliaro, Paola; Gnaldi, Michela; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume provides an overview of the ways the Italian school of quality of life studies addresses well-being and quality of life, from both a substantive and a methodological point of view. It discusses various topics such as those of equitable and sustainable wellbeing, lifestyles, the organization of economy and welfare, as well as aspects related to the measurement of quality of life in small towns, institutional transparency and corruption prevention indicators. Chapters presented in this volume are drawn from papers presented at the conferences of the Italian Association for Quality of Life Studies (AIQUAV) held in Florence, Italy, in 2015 and 2016. The volume is organised into three parts. The first part is devoted to methods and indicators for research on quality of life, the second part to social sustainability, lifestyles, cultural aspects and local applications, and the third to economy, welfare and quality of life. The volume hosts contributions that are interdisciplinaryin scope and mirror the complexity of the globalized world. .
Part I. Methods and Indicators for Quality of Life Research -- Chapter 1. Quantification of Partially Ordered Data and the Evaluation of Financial Literacy (Fattore) -- Chapter 2. Using a Composite Index to Measure Social Inclusion of People with Disabilities (Mazziotta) -- Chapter 3. Measurement of Well-Being in Territories: An Application for Italian Provinces (Costa) -- Chapter 4. Corruption Indicators and Prevention Policies (Carloni) -- Chapter 5. Corruption Prevention: First Evidences from the 2015 RPC Survey for Italian Municipalities (Gnaldi) -- Chapter 6. Transparency and Social-Political Environment in Italy (Galli) -- Chapter 7. The Quality of Life in the Historic Centre of Naples: The Use of PLS-PM Models to Measure the Well-Being of the Citizens of Napels (Cataldo) -- Chapter 8. The Incidence of Sin Taxes: Evidence from Italy (Di Bella) -- Chapter 9. With Whom Do We Compare Our Income? The Effect of Gendered Income Comparisons on Subjective Well-Being (Ravazzini) -- Part II. Social Sustainability, Lifestyle, Cultural Aspects and Local Applications -- Chapter 10. Sustainability of Well- Being: An Analysis of Resilience and Vulnerability through Subjective Indicators (Bachelet) -- Chapter 11. A Multi-Stakeholder FrameBES Data: A Focus on Health in South Tyrol (Salustri) -- Chapter 12. Food Styles and Well-Being of Italian People: A Contribution from Official Statistics (Corazziari) -- Chapter 13. Food, Eating Behaviors and Quality of Life (Di Francesco) -- Chapter 14. Food Waste and Quality of Life (Corvo) -- Chapter 15. Culture Creativity and Quality of Life in Old Age (Cristini) -- Chapter 16. The Past Empowering the Present: Intergenerational Solidarity Improving Quality of Life (Dryjanski) -- Chapter 17. Intergenerational Sustainable Tourism and Quality of Life (Albanese) -- Chapter 18. Territories and Landscapes: Place Identity, Quality of Life and Psychological Well-Being in Rural Areas (Ferrari) -- Part III. Economy, Welfare and Quality of Life -- Chapter 19. Economic Growth, Quality of Life, Life Styles and Sustainability: Correlations and New Variable to be Considered as Indicators (Ciani Scarnicci) -- Chapter 20. European Welfare State: Does Decentralization Affect Poverty? (Coli) -- Chapter 21. Decent Work Principles and Job Quality Criteria to Improve Sustainable and Equitable Well-Being (Conigliaro) -- Chapter 22. Patient Satisfaction and Uncertainty in Illness in Oncology (Giammanco) -- Chapter 23. The Environmental, Economic and Social Sustainability of Energy Sources (Borelli) -- Chapter 24. Sports and Physical Activities in Europe: How to Measure Active Life Styles (Mussino) -- Chapter 25. The Emergence of the Middle Class and Improving Quality of Life in the Global South (Bianco).
Keywords: Quality of life; Social sciences -- Statistical methods; Community psychology; Sociology -- Methodology; Quality of Life Research; Statistics in Social Sciences, Humanities, Law, Education, Behavorial Sciences, Public Policy; Community Psychology; Sociological Methods